HUBUNGAN ANTARA DERAJAT PENYAKIT OSTEOARTRITIS LUTUT DENGAN NEUTROPHIL LYMPHOCYTE RATIO PADA PASIEN DI RUMAH SAKIT UMUM AL FAUZAN JAKARTA PERIODE 2019-2021 - Feby Triana Suhaida (2022)
Knee osteoarthritis is a degenerative disease that occurs as a result of progressive destruction or loss of articular cartilage. In OA, the severity of the disease is determined based on clinical conditions and supporting examinations such as Ultrasonography (USG). However, this examination has an unaffordable price and cannot detect the severity of OA in the early stage, so alternative markers are needed that can reflect the severity of the disease such as the Neutrophil Lymphocyte Ratio (NLR). This study aims to determine the relationship between the degree of knee OA disease and the Neutrophil Lymphocyte Ratio (NLR). Using a cross-sectional design with a sample of 75 patients taken using the Total Sampling method at Al Fauzan General Hospital Jakarta for the period January 2019 - August 2021. The results showed, the NLR value (< 2.1) in the degree of knee OA mostly had mild degrees of 33 people (71,7%) and on the NLR value (> 2,1) most of them had severe degrees of 17 people (58,6%). The results of the analysis with the Chi-Square test obtained a p-value of 0.018 (<0.05). Based on these results, it can be concluded that has a significant relationship between the grades of knee OA disease and the Neutrophil Lymphocyte Ratio (NLR). This is related to the hypersecretion of inflammatory mediators that cause damage to joint cartilage, which if it occurs for a long time will cause an increase in the severity of knee OA.